Effect of tobacco, alcohol, and smoking habits in oral precancer with histological proven epithelial dysplasia - Seema Nayak; Saumya Chandra; Divya Mehrotra; Sumit Kumar; S.P. Agrawal; Sandeep Kumar; Madhu Mati Goel (Elsevier, 2012)
Objectives: To assess the effect of risk factors tobacco, alcohol, and smoking habits in oral precancer patients with epithelial dysplasia status. Material and methods: The study sample included biopsy proven cases of 29 oral submucous fibrosis (OSMF) and 43 cases of clinical leukoplakia. Histopathological diagnosis was made from formalin fixed paraffin embedded tissues as per WHO criteria. The relevant clinical and demographic details were recorded after interviewing the patients. Risk for tobacco, alcohol and smoking was determined by logistic regression analysis by SPSS software. Results: Presence of epithelial dysplasia was significantly associated with tobacco in OSMF & both tobacco and smoking habits in leukoplakia. In OSMF tobacco was associated with 14.16-fold (95% CI, 1.36-147.07; p < 0.026) and in leukoplakia tobacco was associated with 4.66-fold (95% CI, 1.00-21.63; p < 0.047) and smoking was associated with 9.20-fold (95% CI, 1.65-51.28; p < 0.011) increased risk of epithelial dysplasia. Conclusion: Tobacco consumption was independent risk factor for epithelial dysplasia in OSMF and both tobacco and cigarette smoking were independent factors for epithelial dysplasia in leukoplakia.